Pavia, 1249. Publica Fama and Culpa in the Trial Against the Prison Warders (Italian Review of Legal History, 2017)
The essay regards the study of a verdict in Pavia dating back to 1249. The trial took place in a crucial period of the history of criminal law and criminal procedure and testifies of some changes taking place in the years around the mid-13th century which invest, on the one hand, the themes of imputability and the subjective elements of the crime and, on the other hand, strictly procedural aspects.
Keywords: Inquisitio; fama facti; infamia facti; culpa; history of criminal justice